2011
DOI: 10.1115/1.4004084
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Compressibility on the Aerodynamics of an Inverted Wing in Ground Effect

Abstract: For inverted wings in close ground proximity, such as race car configurations, the aerodynamic ground effect can produce local velocities significantly greater than the freestream and the effects of compressibility may occur sooner than would be expected for a wing that is not close to a ground plane. A three-dimensional computational fluid dynamics study was conducted, involving a modified NASA GA(W)-2 LS [1]-0413 MOD inverted wing with an endplate, to investigate the onset and significance of compressibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Grid inde pendence of the three-dimensional hexahedral mesh þ (approximately 8 x 10 6 cells, y of approximately 1 on the wing) has previously been verified through extensive comparison to experiment. 6 Figure 1 shows the domain extent and an example mesh (for the original wing span). For this study, wing transition was not imposed (as it was in the original experiments) so as to eliminate it as an influence on the results -a real-world racing car wing would feature free transition and future work, consider ing the effect of span on this variable would be useful.…”
Section: Methodsmentioning
confidence: 99%
“…Grid inde pendence of the three-dimensional hexahedral mesh þ (approximately 8 x 10 6 cells, y of approximately 1 on the wing) has previously been verified through extensive comparison to experiment. 6 Figure 1 shows the domain extent and an example mesh (for the original wing span). For this study, wing transition was not imposed (as it was in the original experiments) so as to eliminate it as an influence on the results -a real-world racing car wing would feature free transition and future work, consider ing the effect of span on this variable would be useful.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, additional simulations were run as transient (unsteady RANS) and the flowfields were time-averaged in order to assess the suitability of steady-state simulations for the present investigation. Because of a similar industry standard, all simulations were run as incompressible, although local density changes, particularly in the contact patch region, may have a slight influence on the flow (Doig et al, 2011;Doig, 2014;Keogh et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…According to [11], fluids experience compressible flow effects at Mach numbers greater than 0.3. At hydrogen's high and low pressure/flowrate conditions during the fill-up, 415.00 bar/0.006 kg/s and 360.00 bar/0.002 kg/s respectively (mass flowrate values shown with gram precision), it can be shown that the resulting Mach number are 0.004 for high conditions and 0.002 for low conditions.…”
Section: 2mentioning
confidence: 99%